Determination of Maintenance Priority Based on Analytical Hierarchy Process for Magnetic Resonance Imaging - Nurdono Nurdono; Muhamad Haddin (International Journal of Information Technology and Business, 2026)
Magnetic Resonance Imaging (MRI) is a high-tech medical diagnostic equipment that plays an important role in healthcare, but in its operation it faces problems in the form of very large maintenance costs. This is due to the complexity of MRI technology, where the main unit of MRI is an imported product, while supporting equipment such as UPS, chiller, and AHU system are domestic products, thus impacting the increase in maintenance costs in hospitals and potentially reducing the quality of service. The solution to reduce maintenance costs, because maintenance cost efficiency can increase hospital profits. This study discusses the determination of maintenance priorities on MRI using a multi-criteria-based decision-making model by considering: the age of the MRI, the number of error logs, the condition of supporting equipment, and the expertise of the operator in operating the MRI. The Analytical Hierarchy Process (AHP) method is used with the stages of forming a decision hierarchy, pairwise comparisons, matrix normalization, priority weight calculation, and consistency testing. Data were obtained through questionnaires given to competent respondents, with the object of research at the Orthopedic Hospital, Surakarta, Indonesia. The results of the study indicate that the AHP method can be used to determine MRI maintenance priorities effectively. This is evidenced by the best alternative results, namely the Medium type (0.3372), followed by All Risk (0.3315), and Labor Only (0.3311). The Medium type is the most optimal choice. The AHP method has been proven to provide objective, structured, and accountable recommendations for hospital management in determining maintenance contracts that are appropriate to the technical condition of the equipment and budget constraints.